Patterns and Factors Affecting Social Interaction Among Passengers on Pelni Ship: A Sociological Analysis - Alwi, Alimin (Unika Santu Paulus Ruteng, 2025)
Social interaction on Pelni ships has its own unique characteristics. This study aims to reveal the social interaction between passengers on Pelni ships as a unique social space that is formed during sea voyages in Indonesia. Pelni ships, with their various facilities and passenger classes, serve as a platform for individuals from diverse social, cultural, and economic backgrounds to interact. This research employs a qualitative approach using participatory observation and in-depth interviews with 25 passengers on the Makassar-Baubau-Raha-Kendari route in February 2025 The findings of this study indicate that the ship's space creates unique temporary social relationships, ranging from light conversation, cooperation in joint activities, to minor conflicts due to differences in values and customs. Several factors that influence interaction patterns include the duration of the trip, the layout of the ship, and the socio-cultural values brought by the passengers. In addition, social interaction is also influenced by social status and access to certain facilities, which sometimes reinforces social stratification on the ship. However, in some cases, these differences actually serve as catalysts for solidarity and cooperation among passengers. This study offers insights into the social dynamics within the mobile social space of a Pelni ship, reflecting the diversity of Indonesian society while also highlighting the challenges of maintaining social harmony amid such diversity. These findings are expected to serve as a foundation for improving service design and social policies on board ships to enhance the quality of the passenger experience.